Survey design for quarterly labor force survey in Lao P.D.R. - Norasane, Somsamay
Abstract (This study constructs the sampling design for the Quarterly Labor Force Survey in Law P.D.R using the 2015 Lao Populations and Housing Census as the frame. With provinces as the domain, a two-stage sample selection procedure with villages as the primary sampling units and households as the secondary sampling units is proposed. Primary sampling units are stratified using number of household with 5 strata. The secondary sampling units are selected using systematic sampling. Horvitz-Thompson Estimator was used in estimation. Efficiency of estimates from the sampling scheme are assessed through simulation studies with inputs from 2010 Lao Labour Force and Using Child labour survey).
May 2017.
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Sampling (Statistics); Social surveys